Total elbow arthroplasty following traumas: mid-term results. - Pogliacomi, Francesco; Galavotti, Cristina; Cavaciocchi, Michele; Corradi, Maurizio; Rotini, Roberto; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2014)
Background: Total elbow arthroplasty (TEA) has been normally indicated for chronic inflammatory arthropathy. In the last decades this surgery has also evolved as an acceptable procedure following traumatic lesions of this joint. The aim of this study was to analyze the mid-term outcomes of TEA for the treatment of complex fractures and non-unions of the elbow in selected patients. Methods: Between May 2002 and December 2011, 34 patients with these indications were surgically treated with TEA and divided in two groups. Group 1 included 16 cases of fractures and Group 2 18 of non-union. All patients were clinically assessed using the Mayo Elbow Performance Score (MEPS). A statistical analysis was performed in order to investigate the outcomes of these patients and compare the two groups. Results: Similar results were observed in both groups between operated and non-operated arms. No differences in clinical results were documented between groups. Conclusions: TEA following traumas can be considered as a valid treatment in old patients in complex fractures of the elbow region with low functional demands and in non-unions. Outcomes are influenced by the collaborative capacities of the patients.